POLITENESS AND IMPOLITENESS STRATEGIES USED IN THE “SLEEPING BEAUTY” MOVIE - Wahyuni Juliani; Emeliya Sukma Dara; Filza Afiqah; Sri Wahyuni (Muhammadiyah University of Mataram, 2022)
This research aims to analyze the politeness and impoliteness strategies in The Sleeping Beauty Movie. This research used qualitative method by selecting and collecting data in the Sleeping Beauty movie. After selecting and collecting the data, the researchers identify and analyze word by word conversation among characters and used the concept of Brown and Levinson, Geoffrey Leech, and Bousfield and Locher related to pragmatics study. The result shows that there are 19 examples of politeness strategies, politeness maxims and impoliteness strategies. They are 4 examples of politeness strategies, 8 examples of politeness maxims, 7 examples of impoliteness strategies. The researchers concludes that the positive and impoliteness strategies in the Sleeping Beauty Movie is dominated by positive impoliteness and approbation maxim.Keywords: Impoliteness, Politeness, Pragmatics, Sleeping Beauty Movie, Strategies